Understanding factors influencing home pregnancy test use among women in western Kenya: A qualitative analysis - Christina Mazumder; Annabel Dollah; Rosebel Ouda; Moses Okombo; Judith Nyakina; Monica L. Makia; Julia C. Dettinger; Laurén Gómez; Mary Marwa; Ben Ochieng; Felix Abuna; Claire Gwayi-Chore; et al. (Frontiers in Reproductive Health, 2023)
BackgroundThere are limited data on home pregnancy test use among women in low-and-middle-income countries. A prior survey found that only 20% of women in western Kenya used a home pregnancy test to confirm their pregnancies before going to antenatal care. This qualitative study aims to understand why women do not use home pregnancy tests in early pregnancy.MethodsFrom April 2021 to July 2021, we interviewed women from four antenatal care clinics in Homa Bay and Siaya counties. We recruited women previously enrolled in the PrEP Implementation for Mothers in Antenatal care (PrIMA) study, a cluster-randomized trial that evaluated the best approaches to implementing PrEP in maternal and child health clinics in Western Kenya (NCT03070600). Interviews were conducted via phone, audio recorded, translated, and transcribed verbatim. We coded and analyzed the transcripts to capture factors influencing women's capability, opportunity, and motivation to use home pregnancy tests.ResultsWe conducted 48 semistructured interviews with women aged 21–42 years. Twenty-seven women did not use a home pregnancy test in their most recent pregnancy. Seventeen of these women reported not using a home pregnancy test before. Lack of knowledge, mistrust in the accuracy of tests, preferring to rely on signs and symptoms of pregnancy or get a test from the health facility, cost, and accessibility were key barriers to home pregnancy test use.ConclusionImproving the uptake of home pregnancy testing during early pregnancy will require efforts to enhance community knowledge of test use and associated benefits and reduce cost burdens by making tests more affordable and accessible.